75.0k views
4 votes
What is the result of subtracting the second equation from the first?

8x-4y = -4
-3x+4y = 5



User Zuba
by
5.4k points

2 Answers

3 votes

Answer:

11x - 8y = -9

User Aleris
by
5.5k points
1 vote

Answer:


11x-8y=-9

Explanation:

we have


8x-4y = -4 ----> First equation


-3x+4y=5 ----> Second equation

we know that

To subtract the 2nd equation from the first, negate all three of the second equation terms: 3x-4y=-5

and then adds this result with the first equation


8x-4y = -4\\3x-4y=-5\\-------\\8x+3x-4y-4y=-4-5\\11x-8y=-9

User Jacob Pavlock
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.